A new ‘saccamminid’ genus (Rhizaria: Foraminifera), from 4400 m water depth in the Nazaré Canyon (NE Atlantic) - Da Silva, Ana Aranda; Gooday, Andrew J.; Pearse, Richard B.; Cunha, Marina R. (Zootaxa, 2011)
We describe Bithekammina occulta, a new monothalamous agglutinated foraminiferan (‘saccamminid’) collected in multicore samples at 4400 m on the terrace of the lower Nazaré Canyon on the Portuguese margin. The test is spherical to oval, up to 400 µm in length, with a simple circular aperture. The wall has a very smooth surface with a distinct sheen in reflected light. It is <10 µm thick and composed of very fine agglutinated plate-like clay particles and a thin inner organic layer. The most distinctive feature of the new species is that the test is contained within an agglutinated case (‘secondary test’) composed mainly of larger (10–50 µm) quartz grains. The case is equipped with a long, narrow tube that originates near the aperture of the inner test and presumably acts as a channel through which pseudopodia are deployed. Secondary agglutinated structures have been described in a number of foraminifera, but never before in a ‘saccamminid’.